2013
DOI: 10.4238/2013.october.29.9
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of mutations in the familial Mediterranean fever gene (MEFV) in Turkish patients of the Central Anatolia region: a comparison of two mutation detection system

Abstract: ABSTRACT. The purpose of this study was to determine the spectrum of the most common mutations in the familial Mediterranean fever gene (MEFV) in Turkish patients from the Central Anatolia region, by using two different methods for detecting FMF-associated mutations with different screening panels, and compare our results with other diagnostic molecular genetics centers. A total of 1579 patients were analyzed. Genomic DNA from 304 patients was tested for 6 common mutations located in exon 2 (E148Q), and exon 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our results were found to be compatible with the results of other studies conducted in various regions of Turkey. [13][14][15][16] Out of 65 patients with the combination of other frequent mutations, 30 of these patients also showed R202Q mutation. Furthermore, out of these 65 patients, 37 individuals were detected to carry the M694V mutation with the highest ratio (56.92% The same results were also valid for other common mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were found to be compatible with the results of other studies conducted in various regions of Turkey. [13][14][15][16] Out of 65 patients with the combination of other frequent mutations, 30 of these patients also showed R202Q mutation. Furthermore, out of these 65 patients, 37 individuals were detected to carry the M694V mutation with the highest ratio (56.92% The same results were also valid for other common mutations.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Table 1 shows the allele frequencies of some SNPs (rs224222, rs3743930, rs28940580) that might play a role in the development of FMF (Zamani et al, 2013;Abedi et al, 2013;Cetin et al, 2014;Deniz et al, 2014). According to HapMap (http://hapmap.ncbi.nlm.nih.gov/) and dbSNP data (http://www.ncbi.nlm.nih.gov/SNP/), our primary results showed that the allele frequencies of specific mutations for FMF are different frequencies in CEPH (The Centre de'Etude du Polymorphism Humain) and CEU (Utah residents with Northern and Western European ancestry from the CEPH collection).…”
Section: Prevalent Genetic Disorders In Cyprusmentioning
confidence: 99%